Consumers’ Online Purchase Intention: A Study among University Students in Malaysia - Yee, Shi Wuan (2011)
E-commerce is one of the crucial trading methods in the worldwide. Hence, it is important to understanding consumers’ online purchase intention. This research aims to examine factors that influencing consumers’ online purchase intention among university students in Malaysia. Besides, the most significant factor would be determined in this research and recommendations would be provided. Moreover, quantitative research method was used in this research by distributed online questionnaires to 250 Malaysian university students who aged between 20 – 29 years old, and has online purchase experience. The convenience sampling and snowball sampling technique would be applied in this research. In addition, the findings showed that trust, perceive usefulness and subjective norm has significant to predict online purchase intention. However, perceived ease of use and perceived enjoyment were not significant to predict the variance in online purchase intention. The findings also have revealed that subjective norm is the most significant predict factor. On the other hand, large sample size and longitudinal study are recommended for future research.